2001
DOI: 10.1006/dbio.2001.0475
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Localization of Caveolin-1, and the Presence of Membrane Rafts, in Mouse and Guinea Pig Spermatozoa

Abstract: In somatic cells, caveolin-1 plays several roles in membrane dynamics, including organization of detergent-insoluble lipid rafts, trafficking of cholesterol, and anchoring of signaling molecules. Events in sperm capacitation and fertilization require similar cellular functions, suggesting a possible role for caveolin-1 in spermatozoa. Immunoblot analysis demonstrated that caveolin-1 was indeed present in developing mouse male germ cells and both mouse and guinea pig spermatozoa. In mature spermatozoa, caveolin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
130
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(140 citation statements)
references
References 55 publications
(67 reference statements)
10
130
0
Order By: Relevance
“…Speract from the egg jelly of S. purpuratus activates GC [4 9, 50 ] (reviewed in [5,51]). In contrast to mouse and guinea pig sperm [42], SU sperm microdomains do not contain the caveolae marker caveolin (a 21-24 kDa integral membrane protein), although caveolin is present in the whole sperm lysate. As the speract receptor, a GPI-anchored protein and G sα coimmunoprecipitated together, Ohta et al, [52] suggested that this LD-DIM could constitute a signaling complex involved in regulating sperm respiration, motility and the acrosome reaction (AR) [52].…”
Section: Susac Association With Micro Domainsmentioning
confidence: 83%
See 1 more Smart Citation
“…Speract from the egg jelly of S. purpuratus activates GC [4 9, 50 ] (reviewed in [5,51]). In contrast to mouse and guinea pig sperm [42], SU sperm microdomains do not contain the caveolae marker caveolin (a 21-24 kDa integral membrane protein), although caveolin is present in the whole sperm lysate. As the speract receptor, a GPI-anchored protein and G sα coimmunoprecipitated together, Ohta et al, [52] suggested that this LD-DIM could constitute a signaling complex involved in regulating sperm respiration, motility and the acrosome reaction (AR) [52].…”
Section: Susac Association With Micro Domainsmentioning
confidence: 83%
“…Sea urchin sperm membrane microdomains are physiologically functional [34], as has been shown in mammals [41][42][43][44] and the ascidian Ciona intestinalis [45]. Both SUsAC and tmACs, have been found associated with membrane microdomains (reviewed in [46,47]).…”
Section: Susac Association With Micro Domainsmentioning
confidence: 98%
“…Similarly, we used Na ϩ /K ϩ ATPase as a marker for Triton X-100-soluble proteins (26) and found that it was exclusively present in this fraction. We also probed the membranes with ␣-actinin and caveolin 1, which are two proteins that generally segregate to Triton X-100-insoluble fractions (27,28). We found that caveolin 1 was present exclusively in the Triton X-100-insoluble portion of extracts from both undifferentiated and differentiated keratinocytes.…”
Section: Distribution Of Ilk In Fractionated Keratinocytementioning
confidence: 96%
“…A few marker proteins were described for lipid rafts: caveolin which is a cholesterol interacting protein involved in clathrin independent endocytosis of caveolae (Elliott et al, 2003;Nabi and Le, 2003) and flotillin, whose function is not yet completely understood, although it has a prohibitin homology (PHB) domain that is supposed to interact with the raft by constituting a primordial lipid recognition motif (Morrow and Parton, 2005). Both caveolin and flotillin are present in mammalian sperm (Travis et al, 2001;Cross, 2004;Sleight et al, 2005). In porcine sperm, both proteins were detected in the plasma membrane over the acrosome in a dispersed, punctuated pattern (van Gestel et al, 2005a).…”
Section: Sperm Membrane Microdomainsmentioning
confidence: 99%